Nothing: three inquires in Buddhism - Boon, Marcus (Three inquires, 2015)
To live in a glass house is a revolutionary virtue par excellence : Marxism, Buddhism, and the politics of nonalignment / Marcus Boon -- Enlightenment, revolution, cure : the problem of praxis and the radical nothingness of the future / Eric Cazdyn -- Buddhaphobia : nothingness and the fear of things / Timothy Morton